2018
DOI: 10.3233/cbm-181329
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bmi-1-mediated NF-κB signaling pathway on the stem-like properties of CD133+ human liver cancer cells

Abstract: Down-regulating Bmi-1 may inhibit the biological properties of CD133+ LCSC by blocking NF-κB signaling pathway, which lays a scientific foundation for the clinical treatment of liver cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Because the lack of p16Ink4a, the retinoblastoma product (pRB) can be phosphorylated by the cyclin D/Cdk4/6 complex, which allows the transcription factor (E2F)-dependent transcription that leads to the progression of cell cycle and synthesis of DNA. Ma et al ( 27 ) found that Bmi - 1 may play an important role in the progression of liver cancer by the independent pathway of p16Ink4a to regulate the cell multiplication. Furthermore, murine double minute 2 (MDM2)-mediated p53 degradation causes low p53 levels in the absence of p19Arf, thus could prevent cell cycle arrest and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Because the lack of p16Ink4a, the retinoblastoma product (pRB) can be phosphorylated by the cyclin D/Cdk4/6 complex, which allows the transcription factor (E2F)-dependent transcription that leads to the progression of cell cycle and synthesis of DNA. Ma et al ( 27 ) found that Bmi - 1 may play an important role in the progression of liver cancer by the independent pathway of p16Ink4a to regulate the cell multiplication. Furthermore, murine double minute 2 (MDM2)-mediated p53 degradation causes low p53 levels in the absence of p19Arf, thus could prevent cell cycle arrest and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we investigated the role of G-Rg1 in the regulation of NF- κ B activity. Previous studies have indicated that NF- κ B regulates the release of proinflammatory cytokines, and the blockade of NF- κ B activation can decrease the expression of proinflammatory factors [36, 37]. Gao et al also demonstrated that G-Rg1 inhibited inflammation effectively through the inhibition of glucocorticoid receptor-dependent NF- κ B activity [38].…”
Section: Discussionmentioning
confidence: 99%
“…Published articles have shown that CSCs are the main factor in uencing tumor recurrence after treatment and that activation of some protooncogenes in CSCs, such as PCGF4, cause tumor recurrence [7,8]. Moreover, PCGF4 has a key role in EMT (the epithelial-mesenchymal transition), cancer stem cells, and chemotherapy resistance [9][10][11][12][13][14][15][16][17][18]. In head and neck squamous cell carcinoma, PCGF4 + CSCs show cisplatin resistance, with possible relapse after chemotherapy [9].…”
Section: Introductionmentioning
confidence: 99%